The Influence of Accrual Basis Method on PT Elnusa, Tbk’s External Parties in Mids Of Pandemic Covid 19 - Rahman, Abdul; Sari , Hanifah Qianis (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
The covid 19 pandemic has quite a several impacts on various businesses or companies in Indonesia, thus affecting economic growth. This pandemic also affected PT Elnusa whose engaged in natural gas and petroleum. The impact can be seen from the declining external parties (investors) of the company. The decrease of investors to invest in the company will affect the financial rate. The accrual basis method as a provider of financial statements will show the calculation of data from the company’s finances. The accrual basis can be used by investors as an analysis of company growth through finance for the target company. Pandemics that affect the company’s financial rate will be visible in the financial statements using the accrual basis method. Accrual basis provides comprehensive financial statements or all transactions so that they will be clearer and more actual, especially for the company’s external parties. External parties of the company need appropriate and factual financial reports to be able to see the clarity and optimal performance of the company so that it will be an attraction for investors.